Embryotoxicity characterization of the flame retardant tris(1‐chloro‐2‐propyl)phosphate (TCPP) in the invertebrate chordate Ciona intestinalis. Issue 3 (27th January 2021) - Mercurio, Silvia; Messinetti, Silvia; Manenti, Raoul; Ficetola, Gentile Francesco; Pennati, Roberta
Abstract: Tris(1‐chloro‐2‐propyl)phosphate (TCPP) is the most common chlorinated organophosphorus flame retardant in seawater. Due to its chemical features and abundance, TCPP has been classified as a high hazard, and restrictions of use have been set in multiple countries. Despite TCPP being highly present in the marine environment, only a few studies have explored the TCPP impact on the development of marine invertebrates. Ascidians are important invertebrate members of benthic marine communities and reliable model systems for ecotoxicological research. The aim of this study was to assess the adverse effects of TCPP exposure on the embryogenesis of the ascidian Ciona intestinalis . Our results showed that this pollutant affected both muscles and nervous system development. Malformations appeared similar to those reported in other animal models for other flame retardants, suggesting that these molecules could share a common mechanism of action and induce a mixture effect when simultaneously present in the aquatic environment even at sub‐teratogenic concentrations. Abstract : Tris(1‐chloro‐2‐propyl)phosphate (TCPP) is one of the most common flame retardants in seawater. We assessed the TCPP adverse effects on the embryonic development of Ciona intestinalis . Our results showed that exposure to different concentrations of this pollutant affected both muscles and nervous system development in ascidians. Highlights: Tris(1‐chloro‐2‐propyl)phosphate (TCPP) affected ascidian development; TCPP exposure caused malformations in the larval tail, affecting muscle differentiation; TCPP affected neurogenesis, inducing alterations in neural fibers' arrangement.